The dynamics of land use in the province of Kossi, North-West Burkina Faso - Sanogo, Salifou; Karambiri, Bienvenue Lawankilea Chantal Noumpoa; Badini, Mahamoudou; Yanogo, Pawendkisgou Isidore (Penerbit Universiti Kebangsaan Malaysia, 2024)
Land use dynamics are a fundamental variable influencing human activities and the environment. Planning agricultural practices and combating environmental degradation must therefore take this into account. The aim of this study is to understand the environmental transformations that occurred between 1999, 2009 and 2019 as a result of land use dynamics. To achieve this, a methodological approach combining digital processing of 30×30 metre resolution LANDSAT TM temporal images of the years 1999, 2009 and 2019 based on object recognition from fieldwork using Geographic Information System (GIS) tools and a literature review was adopted. The results obtained by analysing the time series of LANDSAT TM images showed that: over the three periods, the area of natural vegetation formations such as open and dense vegetation decreased by more than 21%, while anthropogenic formations increased by 24% in the province of Kossi. For example, 87% of respondents said that bushfires and the increase in the area planted with crops were responsible for environmental degradation. Generally speaking, the natural environment in the Kossi has undergone a major transformation, and human activities are responsible for this. The practice of extensive, space-consuming agriculture by the majority (97.23%) of the population, using unsuitable farming techniques, is the source of the decline in natural formations. Bare soil has declined by more than 40%, which shows that people are using techniques to reclaim degraded land.